2012
DOI: 10.3844/ajbbsp.2012.81.98
|View full text |Cite
|
Sign up to set email alerts
|

Key Parameters of Measles Virus Production for Oncolytic Virotherapy

Abstract: Attenuated measles virus has revealed selective tumor cell killing and is currently tested in clinical trials for the therapy of cancer patients. The amount of infectious particles per dose needed for oncolytic therapy can be more than a million times higher compared to vaccination. This requires highly effective production processes which guarantee the measles virus quantities needed for its use in cancer therapy. Referring to measles virus production itself, several factors are influencing process parameters… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…While these virus particles are stabilized with different agents or are even lyophilized, this stability studies are not representative for measles virus particles under production conditions. The key parameters for MV production for the use in cancer therapy were already discussed in a previous review (Weiss et al, 2012).…”
Section: Ajbbmentioning
confidence: 99%
“…While these virus particles are stabilized with different agents or are even lyophilized, this stability studies are not representative for measles virus particles under production conditions. The key parameters for MV production for the use in cancer therapy were already discussed in a previous review (Weiss et al, 2012).…”
Section: Ajbbmentioning
confidence: 99%
“…Measles virus (MV) is a leading candidate owing to the excellent safety profile of the measles vaccine [2]. However, at least 10 8 infectious MV particles are needed per dose for cancer therapy [3,4] and this has prompted extensive studies focusing on the optimization of upstream processes [5][6][7][8][9][10]. The deeper understanding of MV production gained from these studies has shown that shear stress and aeration play a key role in process productivity [7].…”
Section: Introductionmentioning
confidence: 99%
“…In the first process type, cells are used to produce a therapeutic virus. Vero cells were used as an example for adherent cells used for therapeutic virus production (Weiss et al, 2012; where cell detachment is only crucial during the seeding train to achieve enough cell mass for virus infection. MA104 cells are adherent cells also used in vaccine production and were chosen in the current study as they are very adhesive.…”
Section: Introductionmentioning
confidence: 99%